PENGEMBANGAN LAHAN UNTUK KOMODITAS KOPI ROBUSTA (Coffea carnephora) DI KABUPATEN JEMBER INDONESIA BERDASARKAN POTENSI SUMBER DAYA ALAM - Marhaenanto, Bambang; Andriyani, Idah; kuswardhani, Nita; Tiarawardani, Dwi Anggi Ade (Jurnal Penelitian Sains dan Teknologi Indonesia, 2025)
The Jember Regency has a land area of 3,293.34 km2 (BPS, 2020). Geographically, Jember Regency is located in a strategic area with natural resources that are potential for coffee plantations (Salma et al., 2015). One of them is the robusta coffee variety, which has a bitter taste and high caffeine content. The area of coffee plantations and coffee production decreased from 2019 to 2020 (BPS, 2020). This decline may continue even now. Meanwhile, domestic and international coffee consumption increased from 2020 to 2021 (USDA, 2021). This study uses secondary data for each parameter. Each parameter is classified into its respective land suitability class. After classification, each class is assigned a weight value. The evaluation of land suitability is determined by overlaying raster calculations in ArcGIS 10.3 software to create a map of coffee robusta land suitability classes. The results of data processing indicate that the natural resources for coffee robusta in Jember Regency, based on soil texture, c-organic matter, KTK, nitrogen, phosphorus, potassium, slope gradient, and TBE are predominantly class S1 (highly suitable); the parameters of air temperature, rainfall, and soil pH are predominantly class S2 (moderately suitable); the parameters of dry months and soil depth are predominantly class S3 (marginally suitable). Overall, land suitability is predominantly class S2 (moderately suitable).